Integrating ICT In ESL Classroom: a survey on teachers’ perceptions in using Frog VLE for English lesson / Johan @ Eddy Luaran, Fariha Amalina Zoolkafli and Jasmine Jain - Luaran, Johan @ Eddy; Zoolkafli, Fariha Amalina; Jain, Jasmine (UiTM Press, 2020)
Information and Communication Technology (ICT) is a medium that can be utilised in English lesson. Frog VLE comes into the picture to embrace the use of ICT in Malaysian education. Hence, this research studied the perception in using Frog VLE in English lesson amongst English language teachers in nine secondary schools in Melaka Tengah district. This study employed quantitative research design whereby questionnaires were distributed to the desired sampling in the selected secondary schools. There were 42 respondents who were English language teachers and it was carried out as an online survey. The instrument was a combination of Likert-scale items and one open-ended question. The quantitative data was analysed using SPSS software whilst the open-ended question was analysed using thematic coding analysis. The results revealed that the English language teachers’ level of nowledge was moderately high (M=2.59, SD=0.77). Meanwhile, the teachers’ perceptions in terms of Frog VLE usefulness, ease of use, and students’ motivation in English lesson was moderate (M=3.44, SD=0.56).